(Improving Clove Leaf Oil Quality For Export Using Chemical Deterpenation Process). - Sait, Salya; Hutajulu, Tiurlan Farida (Balai Besar Industri Agro, 1995)
Â In order to improve the export quality of the Indonesian cloveleaf oil,the 66% eugenol containing essential oil produced by the water and steam distillation of old the ground clove leaves (Syzigium aromaticum L.)was deterpenated using two chemical methods of the deterpenation process,i.e. the method based on the formation of water-soluble alkali-phenolates to separate the water-insoluble non-phenolic constituents from the oil and that based on the extration of the soluble oxygenated constituent in dilute ethanol to separate the insoluble terpenes from the oil.Results of the experiments concluded that the method of deterpenation involving the formation of alkali phenolates was comparatively the most favourable process for carring out the quality upgrading of clove leaf oil, since it gave the terpeneless prodict with the highest content of eugenol (92%, compared to 72%obtained from the extration method).However, the method gave the terpene extract, as by-product,on the contrary,with the lowest content of betacaryophyllene (75%,compared to 80% obtained from the other method).